2018
DOI: 10.7595/management.fon.2018.0023
|View full text |Cite
|
Sign up to set email alerts
|

Turnover Intentions and Job Hopping among Millennials in Serbia

Abstract: Research Question: The purpose of this paper is to determine whether the number of jobs the Millennial generation intend to change during their career is larger than that of previous generations; to compare the Millennials’ intention to leave their current job to the previous generations’, and also to examine the relation between the Millennials’ turnover intention and their job satisfaction. Motivation: Millennials keep their resumes updated and have a reputation to be job hoppers (Shaw & Fairhurst, 2008;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
1
14
0
2
Order By: Relevance
“…results found that Gen Z have a higher Turnover Intention (M= 255.7), these findings successfully aligned with earlier studies (Ivanovic& Ivancevic, 2019;Sakdiyakorn et al, 2021) that reported significant generational differences in Turnover Intention. Earlier studies showed that Gen Z has a higher turnover intention than Gen Y.…”
Section: The Variance Between Gen Y and Gen Zsupporting
confidence: 90%
See 1 more Smart Citation
“…results found that Gen Z have a higher Turnover Intention (M= 255.7), these findings successfully aligned with earlier studies (Ivanovic& Ivancevic, 2019;Sakdiyakorn et al, 2021) that reported significant generational differences in Turnover Intention. Earlier studies showed that Gen Z has a higher turnover intention than Gen Y.…”
Section: The Variance Between Gen Y and Gen Zsupporting
confidence: 90%
“…Research has indicated that employees who are part of Generation Y and Z report greater percentages of job satisfaction and may not be as willing to quit as some people believe (Martin, 2017). However, a recent study by Ivanovic and Ivancevic (2019) found that, compared to 48.6% of Generation Y employees, 60.8% of Generation Z employees will leave their present position over the next two years. Employees of Generation Z are not hesitant to quit their jobs to work for an organization that shares their core values and beliefs.…”
Section: Gen Y and Gen Z Differences In Organizational Outcomesmentioning
confidence: 95%
“…Regarding the relationship of Islamic work ethics on turnover intention, the majority of the respondent in this study that categorized as the Millenials was considered as the main reason for the insignificant effect between variables. Ivanovic & Ivancevic (2019) stated that compared to the previous generation, the level of the turnover intention of the Millenials was the largest. Siahaan & Gatari (2020) even mentioned that the highest turnover in companies is found in the Millennials generation.…”
Section: Resultsmentioning
confidence: 99%
“…Suppose the organization has good talent management. The current generation of millennials' job dissatisfaction can negatively impact job security, resulting in the departure of highly qualified personnel and the costs associated with employee turnover and weaker growth prospects (Chillakuri & Mogili, 2018;Ivanovic & Ivancevic, 2019;Yap & Badri, 2020). Baby Boomers tend to be more established in their careers than Millennials and thus will not place the same value on opportunities to learn and develop.…”
Section: Statistics On State Civil Apparatus (Asn) Data From the Stat...mentioning
confidence: 99%